Sexual dimorphism in medulloblastoma features. Issue 4 (12th August 2015) - Zannoni, Gian Franco; Ciucci, Alessandra; Marucci, Gianluca; Travaglia, Daniele; Stigliano, Egidio; Foschini, Maria Pia; Scambia, Giovanni; Gallo, Daniela
Abstract : Aims: Male sex is a risk factor for medulloblastoma (MB), and is also a negative predictor for clinical outcome. The aim of this study was to assess sex differences in tumour biological features and hormone receptor profiles in a cohort of MB patients. Methods and results: Sixty‐four MBs and five normal cerebella were included in the study. Cell proliferation (Ki67), apoptosis (cleaved caspase‐3) and microvessel density (CD31) were evaluated in tumours by immunohistochemistry. Tissues were analysed for oestrogen receptor (ER)α, ERβ1, ERβ2, ERβ5 and androgen receptor (AR) expression. The results demonstrated sex‐specific features in MBs, with tumours from females showing a higher apoptosis/proliferation ratio and less tumour vascularization than tumours from males. MBs were negative for ERα and AR, but expressed ERβ isoforms at similar levels between the sexes. Altogether, these findings indicate that signalling mechanisms that control cell turnover and angiogenesis operate more efficiently in females than in males. The lack of sex differences in the hormone receptor profiles suggests that circulating oestrogens could be the major determinants of the sexual dimorphism observed in MB features. Conclusions: Here, we provide molecular support for epidemiological data showing sex differences in MB incidence and outcome, completely defining the hormone receptor profile of the tumours.